1993
DOI: 10.1021/cm00026a004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of chromium silicalite

Abstract: Infrared spectroscopy (mid-IR), 29Si and 27Al magic angle spinning nuclear magnetic resonance (MAS-NMR), powder X-ray diffraction (PXRD), electron paramagnetic resonance (EPR), and photoacoustic spectroscopy (PAS), in combination, have produced useful information about a series of crystalline MFI-type chromium silicalite, synthesized in a fluoride medium. Aluminum is an impurity and occupies framework sites, as evaluated by the 27Al MAS-NMR. The mid-IR spectra are very similar to the zeolite ZSM-5 with the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…The prepared samples were characterized by means instrumental neutron activation analysis (INAA), nitrogen phsyisorption, powder X-ray diffraction (XRD), UV-vis spectroscopy, Raman spectroscopy (under ambient and under in-situ heating), 29 Si nuclear magnetic resonance (NMR), high-resolution transmission electron microscopy (HR-TEM) and X-ray photoelectron spectroscopy (XPS). Detailed characterization procedures can be found in the Supporting information section.…”
Section: Characterizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prepared samples were characterized by means instrumental neutron activation analysis (INAA), nitrogen phsyisorption, powder X-ray diffraction (XRD), UV-vis spectroscopy, Raman spectroscopy (under ambient and under in-situ heating), 29 Si nuclear magnetic resonance (NMR), high-resolution transmission electron microscopy (HR-TEM) and X-ray photoelectron spectroscopy (XPS). Detailed characterization procedures can be found in the Supporting information section.…”
Section: Characterizationsmentioning
confidence: 99%
“…All the experiments were carried out at least for three times, the results presented here is the average of the three with a standard deviation does not exceed than 3%. 29 Si MAS NMR was performed to study the interaction between Si and Cr in the Cr-TUD-1 sample. The 29 Si MAS NMR spectrum of the calcined siliceous TUD-1 sample is compared with the Cr-5 spectrum in Fig.…”
Section: Catalytic Performance Studymentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that prior to washing there was a peak near 698 cm -1 which suggests that Cr 3+ is coordinated by oxygen moieties of polysiloxanes network [13,14] and thus indicated successful imprinting. After through washing of polymers, the metal-oxygen peak was missing in spectrum indicating the removal of template ions.…”
Section: Resultsmentioning
confidence: 99%